The positivity rates of a novel test in the patients with suspected clostridioides difficile associated diarrhea (Annals of Medical Research, 2021)
Aim: To evaluate the positivity rates of Clostridioides difficile infection (CDI) in the stool samples with a novel test and clinical features of positive cases. Material and Methods: The frequency of C. difficile in a total of 654 stool samples were examined with the BD Max Cdiff Test (Becton Dickinson, USA) between January 2014 and June 2019, and the clinical/demographic characteristics of the positive cases were evaluated in a university hospital.Results: A total 56 (8.56%) samples belonging to 49 cases aged 3-84 year were determined as positive for CDI among total 654 stool samples. Forty-one (89.1%) out of 46 positive cases whose clinical reports were available had a history of hospitalization in the last three months with an average 14.9 days, and 39 patients (84.7%) received antimicrobial treatment in the last three months for an average 12.2 days. It was observed that 40 (86.9%) out of 46 positive cases had at least one underlying chronic disease; and 38 (82.6%) patients used anti-acid agents. Conclusion: In this study, although the risk factors similar to those reported in the international literature were also found for our patients, the incidence of CDI was found to be lower than that reported worldwide. In this context, it is required that the patients in the risk group for CDI must be identified well, and correct and fast methods should be used for diagnosing the infection.
Keywords: Clostridioides difficile; risk factors; antibiotic-associated diarrhea